'Storytelling is storytelling': Resilience, gender and screenwriting in Fair City. Issue 2 (1st June 2022) - Gorton, Kristyn
This article explores the resilience of soap screenwriters and the resilient characters they create in soap opera through interviews with screenwriters on the Dublin-based soap opera Fair City (1989‐present). The article also draws on an interview with Brigie de Courcy, executive producer of Fair City, to highlight the effects of the coronavirus pandemic on soap operas. The interview reveals inherent characteristics of the soap genre, including the habitual viewing of its audience and the ways in which the soap narrative relies on the physical proximity of its actors. The interview also reflects the genre's resilience and the resilience of the people who work within it.